Efficacy and Safety of Radiofrequency Ablation vs. Endoscopic Surveillance for Barrett’s Esophagus With Low-Grade Dysplasia: Meta-Analysis of Randomized Controlled Trials - Wang, Yizi; Ma, Bin; Yang, Shize; Li, Wenya; Li, Peiwen (Frontiers in Oncology, 2022)
Background and Aims Barrett’s esophagus with low-grade dysplasia (BE-LGD) carries a risk of progression to Barrett’s esophagus with high-grade dysplasia (BE-HGD) and esophageal adenocarcinoma (EAC). Radiofrequency ablation (RFA) appears to be a safe and efficacious method to eradicate Barrett’s esophagus. However, a confirmed consensus regarding treatment of BE-LGD with RFA vs. endoscopic surveillance is lacking. Therefore, this study aimed to elucidate the efficacy and safety for RFA vs. endoscopic surveillance in decreasing the risk of BE-LGD progression to BE-HGD or EAC. Methods Relevant studies published before May 1, 2021 were identified by searching relevant medical databases. The primary outcome was the rate of progression BE-LGD to HGD and/or EAC after treatment with RFA and endoscopic surveillance. The secondary outcome was the rate of complete eradication of dysplasia (CE-D) and complete eradication of intestinal metaplasia (CE-IM) after treatment with RFA and endoscopic surveillance. Adverse events were also extracted and evaluated. Results Three randomized controlled trials were eligible for analysis. The pooled estimate of rate of neoplastic progression of BE-LGD to HGD or EAC was much lower in the RFA group than the endoscopic surveillance group (RR, 0.25; 95% CI, 0.07–0.93; P = 0.04), with moderate heterogeneity (I2 = 55%). Subgroup analysis based on progression grade was performed. The pooled rate of progression of BE-LGD to HGD was much lower in the RFA group than the endoscopic surveillance group (RR, 0.25; 95% CI, 0.07–0.71; P = 0.01), with low heterogeneity (I2 = 15%). Although the pooled risk of progression of BE-LGD to EAC was slightly lower in the RFA group than the endoscopic surveillance group (RR, 0.56; 95% CI, 0.05–6.76), the result was not statistically significant (P = 0.65). RFA also was associated a higher rate of CE-D and CE-IM both at the end of endoscopic treatment and during follow-up. However, the rate of adverse events was slightly higher after RFA treatment. Conclusion RFA decreases the risk of BE-LGD progression to BE-HGD. However, given the uncertain course of LGD and the potential for esophageal stricture after RFA, treatment options should be fully considered and weighed. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021266128, identifier PROSPERO (CRD42021266128).